Comparative Examination of Distributive Justice from the Perspectives of Henry George and Allameh Jafari with an Explanation of Its Educational Implications - Mehdinia Firouzjaei, Fereshteh; Khatirpasha, Kiumars; Rasouli , Seyedah Esmat (Assessment and Practice in Educational Sciences, 2024)
The present study conducts a comparative examination of distributive justice from the perspectives of Henry George and Allameh Jafari, with an emphasis on outlining their educational implications. This research is a comparative study that adopts qualitative methods. At the outset, the researcher discusses the general foundations of the study, namely the importance of justice in individual and social life. By presenting the research literature, the theoretical foundations of the study are explained from the two viewpoints of Henry George and Allameh Jafari, including the conceptual analysis of justice and distributive justice and its impact on society. The research methodology is descriptive–analytical and comparative, and required information was collected and evaluated using Bereday’s model. The statistical population consists of all books and articles written on distributive justice from the perspectives of Henry George and Allameh Jafari and the educational implications derived from these two viewpoints. Based on the findings of the present study: Henry George’s view of distributive justice is grounded in the belief that land and natural resources naturally belong to all human beings. He argues that governments should use land rent and the income generated from it to fund public services so that support can be distributed fairly among all citizens. Allameh Jafari’s perspective on distributive justice emphasizes that human nature encompasses diverse emotions and sentiments. George’s orientation toward distributive justice reflects a critical approach and discourse-based perspective, while Allameh Jafari’s view is characterized by moderation.